Pembelajaran Bahasa Arab Komunikatif Melalui Media Pembelajaran Online: Peluang dan Tantangan - Abdullah, Safri (IAIN Bone, 2020)
Communicative Arabic learning through online learning media is an Arabic learning activity that can be carried out in different times and places because of the use of online-based learning technology. The learning process certainly has practical implications for the communicative dimension of Arabic, be it constructive in the form of opportunities or destructive in the form of challenges. The opportunities for communicative Arabic learning through online learning media are the more development of network-based information technology, the increasing number of choices for online Arabic learning applications, and the increasing number of online Arabic learning websites. The challenges of learning communicative Arabic through online learning media are the uneven reach of the internet network in all areas and the unstable internet network at any time, the limited ability of human resources who can carry out communicative Arabic learning through online learning media, and the weakness the economic ability of some students in participating in communicative Arabic learning through online learning media.